A retrospective study of in‐hospital cardiac arrest. Issue 4 (2nd May 2016) - Fujiwara, Shinsuke; Koike, Tomotaka; Moriyasu, Megumi; Nakagawa, Masashi; Atagi, Kazuaki; Lefor, Alan K.; Fujitani, Shigeki; ,
Abstract : Aim: In‐hospital cardiac arrest is an important issue in health care today. Data regarding in‐hospital cardiac arrest in Japan is limited. In Australia and the USA, the Rapid Response System has been implemented in many institutions and data regarding in‐hospital cardiac arrest are collected to evaluate the efficacy of the Rapid Response System. This is a multicenter retrospective survey of in‐hospital cardiac arrest, providing data before implementing a Rapid Response System. Methods: Ten institutions planning to introduce a Rapid Response System were recruited to collect in‐hospital cardiac arrest data. The Institutional Review Board at each participating institution approved this study. Data for patients admitted at each institution from April 1, 2011 until March 31, 2012 were extracted using the three keywords "closed‐chest compression", "epinephrine", and "defibrillation". Patients under 18 years old, or who suffered cardiac arrest in the emergency room or the intensive care unit were excluded. Results: A total of 228 patients in 10 institutions were identified. The average age was 73 ± 13 years. Males represented 64% of the patients (82/146). Overall survival after in‐hospital cardiac arrest was 7% (16/228). Possibly preventable cardiac arrests represented 15% (33/228) of patients, with medical safety issues identified in 8% (19/228). Vital sign abnormalities before cardiac arrest were observed in 63% (138/216) of patients. Conclusions: Approximately 60% of patients had abnormal vital signs before cardiac arrest. These patients may have an improved clinical outcome by implementing a Rapid Response System.